FACTORS CAUSING NON-BREASTFEEDING IN CHILDREN UNDER SIX MONTHS OF AGE IN DISTRICT NOWSHERA, PAKISTAN - Nawaz, Rab; Rehman, Shafiq ur; Nawaz, Shah; Mohammad, Taj (Journal of Ayub Medical College Abbottabad, 2009)
Background: In developing countries bottle feeding has emerged a big public health problem while in developed countries the trend is opposite. Prevalence of breast feeding in Pakistan is 90- 98% but in some subgroups of population it is as low as 60-80%. The objectives of the study were to determine the causes of non breast feeding in children less than six months of age in district Nowshera, and assess practice of starting first breast feeding to the newborn. Methods: A cross sectional study was conducted in ten union councils of district Nowshera. A total of 305 children under six month age were selected by simple random method. Data was collected on pre-designed questionnaire and analysed by descriptive statistics. Results: The study included 198 children from rural and 107 from urban areas. Mothers/guardians of 71.8% children were uneducated. Causes of non breast feeding included perception of mothers of having insufficient milk (45.9%), working mothers (18.4%), mothers with chronic diseases (13.1%), children with congenital or acquired diseases (17%), mothers having next pregnancy (3.61%) whose mothers have been died (0.98 %) and twin babies (0.98%). On the other hand, 61% babies started breast feeding on first day, 19% on second, 10.8% on third and 3.9% after third day while 5.2% babies got no breast feeding at all. Conclusion: Main causes of non-breastfeeding in less than six month age are perception of having insufficient milk, working women and twin babies. Keywords: Breast feeding; Bottle feeding, Public Health Problem, Prevalence